Understanding Fatwa over the Variety of Particular Opinions in Islamic Law | فقه الفتوى على خلافيات الفروع - Muhammad Faishal (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2017)
This paper endeavors to separate between fundamental sides of Islam and its branches, to explain approaches of law schools leaders (aimmatu al-madhaahib) over debatables thinks. Every school was not established following appetite of its founder, indeed every school and whole opinions herein were connected methodologically by golden transmissions (salaasil dzahabiyyah) unto Prophet PBUH, showing urgency of unfanatic character to such opinion, denying who just group of people with sinners, apostators, or performing evil-doings only base on such opinion that they have betrayed their school. In fact, this matter is fluid, and one duties of scholars who issuing legal opinion (fatwa) is twinning all-oriented, not separating peoples. Next, verdict of the judge in such case and its application over public with particular opinion or school has ultimately finished different opinions herein. No one who is uncovered this verdict, then they must follow it denying social conflict performs, showing that the verdict is reliable opinion over other differences by reffering toward Dar al-Ifta al-Mishriyyah. The approaches of research on Dar al-Ifta and their roles are by their publications, interviewing some trustees who answer religious questions from the public and its impacts to protect islamic culture and stability in Egypt. The research concluded that Dar al-Ifta model of issuing fatwa is the most appropriate.